RESPON TANAMAN KEDELAI TERHADAP PUPUK HAYATI MIKORIZA ARBUSKULA HASIL REKAYASA SPESIFIK GAMBUT - Iwan Sasli (Agrovigor, 2013)
The objectives of  this research were to study the  effectiveness of arbuscular mycorrhizal biofertilizer on growth and yield of soybean in peat soil. The  experiment was arranged in a Split-Plot Design  with factorial pattern, consisting of two factors and three replications. The first factor was Mycorrhizal consisted  of the levels: without mycorrhizae, mycorrhizal from biofertilizer, and indigenous mycorrhizal propagule from  pineapple’s rhizosphere were as main-plot.  Dosage of phospate fertilizer  were as sub-plot consisted of:  100, 75,  50, and 25 kg P2O5.ha-1.  The research showed that the mycorrhizal biofertilizer can improve plant growth and increase the some variables, such as plant heights, days to flowering, number of productive branches, dry wight of 100 seeds, number of pods of plant, and the percentage of plant to mycorrhizal dependency. It can be concluded that the arbuscular mycorrhizal specific of peat can be developed as a biologiocal fertilizer and cope with limited nutrient in peat soils and to improve the efficiency of phopate fertilizer.Keyword : fertilizzer, mycorrhyzal,  peat, soybean